Time to success & its prognostic factors among patients underwent myringoplasty in Kelantan - Badrudin, Emy Asmar (2016)
Introduction: Myringoplasty is a surgical procedure which is use to repair a perforation in the tympanic membrane. Most common indications are to prevent further infection of the ear via external auditory canal and to improve hearing. Objectives: This study was conducted to determine the median time to success in myringoplasty as well as to compare the median time to success in myringoplasty between groups and also to identify the prognostic factors of success in myringoplasty among patients in Kelantan. Methods: A retrospective cohort study was carried out on 215 patients having tympanic membrane perforations and underwent myringoplasty within the period of January 2006 to December 2015. From the day of surgery patients were retrospectively followed up at 3, 6, 9, 12 and 24 months. All the information needs had been retrieved from the operation’s note and patient’s progress sheet. Time when patients achieved complete closed of perforation with normal hearing was considered as time to success while those who were lost to follow up as well as failure case were censored observation. Results: Kaplan Meier analysis showed that overall median time to success in myringoplasty was 19.9 (95%CI: 13.6, 44.0) months. There were significant different of time to success between groups for variable age, occupation, marital status, smoking status, postoperative URTI, tympanosclerosis and smoking status. Multiple Cox Proportional Hazard Regression revealed that age, gender, smoking status, upper respiratory tract infection, size of perforation, affected side, graft used and rank of surgeon were significantly associated with success rate of myringoplasty. Conclusion: Success of a myringoplasty appeared to be lower than commonly quoted success rates to the clients in taking consent due to different of patient’s selection criteria, the definition of success used as well as the duration of follow up time after surgery. Time to success, postoperative expected outcome & the prognostic factors should be properly counselled when taking into account of various definitions of success as unrealistic patient expectation is the contraindications for repairing tympanic membrane through myringoplasty.